2010
DOI: 10.3844/ajptsp.2010.14.23
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Effects of Coenzyme Q10 in Experimentally Induced Hypercholesterolemic Model in Female Rats

Abstract: Problem statement: Hyperlipidemia is well known to play a main role in the development of atherosclerosis. It is characterized by abnormally elevated cholesterol, triglyceride, low density lipoprotein cholesterol and very low density lipoprotein cholesterol levels in the blood. It has been recognized for many years that hypercholesterolemia is a major risk factor for cardiovascular diseases such as atherosclerosis, myocardial infraction, heart attacks and cerebrovascular diseases. In recent years, Coenzyme Q10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Hyperlipidemia is an important factor for atherosclerosis that leads to heart attack (obstruction occurs in the coronary arteries) and stroke (obstruction occurs in the arteries of the brain) [ 228 230 ]. Chen et al [ 231 ] suggested the andrographolide as candidate therapeutic agent for atherosclerosis based on their research result.…”
Section: Potential Pharmacologymentioning
confidence: 99%
“…Hyperlipidemia is an important factor for atherosclerosis that leads to heart attack (obstruction occurs in the coronary arteries) and stroke (obstruction occurs in the arteries of the brain) [ 228 230 ]. Chen et al [ 231 ] suggested the andrographolide as candidate therapeutic agent for atherosclerosis based on their research result.…”
Section: Potential Pharmacologymentioning
confidence: 99%
“…The increase in lipids can cause plaques to grow over time and lead to obstructions in blood flow. If an obstruction occurs in the coronary arteries, it could result in a heart attack, and, if an obstruction occurs in the arteries of the brain, it could lead to stroke (Al‐Attar, ). Hence, it is important to actively decrease blood lipid for prevention and cure cardiovascular and cerebrovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Chew et al shows that Q10 have no effect on lipid profile [37]. In chew et al study participants were typically overweight with satisfactory glycemic and lipid control while Q10 appears to be effective in hypercholesterolemic condition [38]. Q10 also significantly reduce Lp (a) but the magnitude of the effect variable among subjects, with some patients show a marked decrease and others only marginal change occur.…”
Section: Discussionmentioning
confidence: 97%